Analysis of Budget Realization Reports to Assess Financial Performance at the Malang Regency Bapenda Office for the 2021-2025 Period - Nining Dewi Maulida; Riyan Maulana; Doni Astofian; Rudi Tamrin Hasbulloh; Erna Resmiatini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The Regional Revenue Agency (BAPENDA) of Malang Regency is a vital supporting agency in optimizing regional fiscal, but its budget management often faces challenges from macroeconomic fluctuations. This study aims to evaluate the financial performance of BAPENDA Malang Regency for the 2021–2025 period through the Budget Realization Report (LRA). The research method used is a descriptive quantitative approach by analyzing the effectiveness ratio of Regional Original Revenue (PAD), the expenditure efficiency ratio, and the expenditure harmony ratio. The research findings show that the PAD effectiveness ratio tends to fluctuate but is highly adaptive; reaching a peak in 2021 (>100%) and soaring to 817.70% in 2025 thanks to innovations in digitalization of tax services. From the aspect of expenditure efficiency, budget absorption consistently moves high, ranging from 89.36% to 98.39%, reflecting optimal utilization of funds without any budget wastage. Meanwhile, the expenditure harmony ratio shows dominance in the Regional Government Affairs Support Program with an average of above 75%. This is considered reasonable and harmonious considering the characteristics of the agency as a revenue collector that relies on the capacity of the apparatus and digital administration systems. This study concludes that the financial performance of the Malang Regency BAPENDA is categorized as very reliable and adaptive, where strengthening internal expenditure allocations has proven linear in encouraging the optimization of regional revenue revenue achievement.